Cancer treatment induces neuroinflammation and behavioral deficits in mice - Demos-Davies, Kimberly; Lawrence, Jessica; Rogich, Allison; Lind, Erin; Seelig, Davis (Frontiers in Behavioral Neuroscience, 2023)
Cancer survivors are increasingly diagnosed with a syndrome of neurocognitive dysfunction termed cancer-related cognitive impairment (CRCI). Chemotherapy and radiation therapy have been implicated in CRCI; however, its underlying pathogenesis remains unclear, hindering effective prevention or treatment. We used the hairless strain SKH1 (11-12-week-old) and treated the mice with radiation to the right hindlimb, doxorubicin (a chemotherapy agent), concurrent radiation and doxorubicin, or no treatment (control). Neurocognition was evaluated via standardized behavioral testing following treatment. Mice were subsequently humanely euthanized, and plasma and brains were collected to identify inflammatory changes. Mice treated with radiation, doxorubicin, or both radiation and doxorubicin demonstrated equivalent hippocampal dependent memory deficits and significant increases in activated microglia and astrocytes compared to control mice. Doxorubicin-treated mice had significantly increased plasma IL-6 and failed to gain weight compared to control mice over the study period. This study demonstrates that non-brain directed radiation induces both gliosis and neurocognitive deficits. Moreover, this work presents the first characterization of SKH1 mice as a relevant and facile animal model of CRCI. This study provides a platform from which to build further studies to identify potential key targets that contribute to CRCI such that strategies can be developed to mitigate unintended neuropathologic consequences associated with anticancer treatment.